A gland of diverse pathology and unpredictable behaviour: our experience of primary submandibular gland malignancies. Issue 10 (October 2018) - Rajappa, S.K.; Bhakuni, Y.S.; Ram, D.; Shukla, H.; Ranjan, R.; Dewan, A.; Dabas, S.; Dewan, A.K.
Abstract: Submandibular gland tumours are relatively uncommon tumours and demonstrate diverse histological types and a variable prognosis. The aim of this study was to analyze our experience with submandibular malignancies over a period of 6 years (January 2009 to December 2015). Patient data from the 6-year period were reviewed retrospectively and 51 patients with submandibular malignancies were identified. Demographic data, clinicopathological details, treatment received, complications, and follow-up were recorded. The mean age of the 51 patients at presentation was 49.1 years. They were followed up for a mean 20.3 months. Nine of 47 patients (19.1%) developed distant metastasis during follow-up, while only three (6.4%) developed local recurrence. Disease-free survival at 2 years was 69.7% and overall survival at the end of 2 years was 77.8%. Actuarial 5-year survival was 57.8% when all subtypes were considered. The overall mean time to recurrence was 10 months (6–24 months). Nodal positivity was the only prognostic factor that was significant on multivariate analysis, while age, sex, perineural invasion, and grade were not. With advances in surgical and radiotherapy techniques, loco-regional control rates have improved greatly; however, effective adjuvant treatment to prevent systemic relapse is still lacking.